2021
DOI: 10.1158/1078-0432.ccr-20-3417
|View full text |Cite
|
Sign up to set email alerts
|

An Immune Risk Score Predicts Survival of Patients with Acute Myeloid Leukemia Receiving Chemotherapy

Abstract: Purpose: Prediction models for acute myeloid leukemia (AML) are useful, but have considerable inaccuracy and imprecision. No current model includes covariates related to immune cells in the AML microenvironment. Here, an immune risk score was explored to predict the survival of patients with AML.Experimental Design: We evaluated the predictive accuracy of several in silico algorithms for immune composition in AML based on a reference of multi-parameter flow cytometry. CIBERSORTx was chosen to enumerate immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Although the prognostic significance of most immune cell types in AML remains to be elucidated, a similar trend has been seen in recent studies on adult AML [42][43][44]. For instance, for adult AML patients treated with chemotherapy, a relatively high proportion of T-and NK-cells in the bone marrow at diagnosis has been associated with improved survival, while the proportion of Tregs has been associated with poor prognosis [42][43][44]. For pediatric AML, such data are not available in literature yet.…”
Section: Immune Cells In the Tmesupporting
confidence: 63%
See 2 more Smart Citations
“…Although the prognostic significance of most immune cell types in AML remains to be elucidated, a similar trend has been seen in recent studies on adult AML [42][43][44]. For instance, for adult AML patients treated with chemotherapy, a relatively high proportion of T-and NK-cells in the bone marrow at diagnosis has been associated with improved survival, while the proportion of Tregs has been associated with poor prognosis [42][43][44]. For pediatric AML, such data are not available in literature yet.…”
Section: Immune Cells In the Tmesupporting
confidence: 63%
“…Accordingly, cytotoxic T-cells, memory T-cells, T-helper 1 cells, follicular helper T-cells, NK-cells, B-cells, and M1-macrophages have been associated with prolonged survival, while high densities of regulatory T-cells (Tregs), M2-macrophages, myeloid-derived suppressor cells, and neutrophils have been correlated with poor prognosis [23,[39][40][41]. Although the prognostic significance of most immune cell types in AML remains to be elucidated, a similar trend has been seen in recent studies on adult AML [42][43][44]. For instance, for adult AML patients treated with chemotherapy, a relatively high proportion of T-and NK-cells in the bone marrow at diagnosis has been associated with improved survival, while the proportion of Tregs has been associated with poor prognosis [42][43][44].…”
Section: Immune Cells In the Tmementioning
confidence: 68%
See 1 more Smart Citation
“…There are also numerous existing models for adult AML early prediction or risk stratification, which have been compared to the FGL model corresponding to different aspects of modeling ( Supplementary Table S8 ). For the immune risk score model proposed for adult AML ( Wang Y. et al, 2021 ), we did not succeed in validating it in the TARGET dataset (data not shown). The inconsistency might be induced by the differences in the immune microenvironment of AML tumors between adults and children.…”
Section: Discussionmentioning
confidence: 95%
“…In AML, the current riskassessment classification 1 and prognostication are still predominantly focused on cytogenetic and molecular alterations, which are historically known to influence the sensitivity of leukemic cells to conventional chemotherapy. However, based on the compelling preclinical data regarding the fundamental impact of tolerogenic tumor microenvironment mechanisms in dysregulating patients' immune response, the prognostic significance of the immune landscape is recognized as being increasingly important in AML, revealing that immune-related genes may predict survival (10). Based on these premises, it is time to move in the direction of a paradigm shift with the ambition to refine stratification and prognostication of AML patients that incorporates an immunological-driven biological approaches.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%